Introduction: Future of Globalization?. Issue 2 (2nd April 2020) - Harris, Jerry; Hrubec, Marek
ABSTRACT: The text is an introduction to the symposium on "Future of Globalization?" for International Critical Thought . It includes a selection of four articles developed after their presentation at the 2019 conference of the Network for Critical Studies of Global Capitalism in Beijing, written by scholars from China, Czech Republic, UK and USA, focusing on issues of transnational capital, China–US tensions, China's and world's reform, and ideology evolution in globalization.